The hepatic microenvironment essentially determines tumor cell dormancy and metastatic outgrowth of pancreatic ductal adenocarcinoma. (2nd January 2018) - Lenk, Lennart; Pein, Maren; Will, Olga; Gomez, Beatriz; Viol, Fabrice; Hauser, Charlotte; Egberts, Jan-Hendrik; Gundlach, Jan-Paul; Helm, Ole; Tiwari, Sanjay; Weiskirchen, Ralf; Rose-John, Stefan; et al.
ABSTRACT: Pancreatic ductal adenocarcinoma (PDAC) is often diagnosed when liver metastases already emerged. This study elucidated the impact of hepatic stromal cells on growth behavior of premalignant and malignant pancreatic ductal epithelial cells (PDECs). Liver sections of tumor-bearing KPC mice comprised micrometastases displaying low proliferation located in an unobtrusive hepatic microenvironment whereas macrometastases containing more proliferating cells were surrounded by hepatic myofibroblasts (HMFs). In an age-related syngeneic PDAC mouse model livers with signs of age-related inflammation exhibited significantly more proliferating disseminated tumor cells (DTCs) and micrometastases despite comparable primary tumor growth and DTC numbers. Hepatic stellate cells (HSC), representing a physiologic liver stroma, promoted an IL-8 mediated quiescence-associated phenotype (QAP) of PDECs in coculture. QAP included flattened cell morphology, Ki67-negativity and reduced proliferation, elevated senescence-associated β galactosidase activity and diminished p-Erk/p-p38-ratio. In contrast, proliferation of PDECs was enhanced by VEGF in the presence of HMF. Switching the micromilieu from HSC to HMF or blocking VEGF reversed QAP in PDECs. This study demonstrates how HSCs induce and maintain a reversible QAP in disseminated PDAC cells, while inflammatory HMFs foster QAP reversal and metastatic outgrowth. Overall, the importance of the hepatic microenvironment in induction and reversal of dormancy during PDAC metastasis is emphasized.